INVESTIGATION OF ANTIVIRAL POTENTIAL OF LICORICE (GLYCYRRHIZA GLABRA L.) CRUDE EXTRACT AGAINST TOBACCO MOSAIC VIRUS - M. H. Ghodoum Parizipour; A. G. Shahriari2 (Journal of Animal and Plant Sciences, 2020)
Tobacco mosaic virus (TMV) is a devastating plant RNA virus infecting a wide range of plants causing considerable losses to agriculture products. Various dissemination means of TMV makes it particularly difficult to control. Application of plant-derived antiviral compounds has gained attention as one of the new control measures against viral diseases. This study was conducted to examine the antiviral effects of licorice (Glycyrrhiza glabra L.) crude extract (LCE) against TMV. To this end, TMV particles were purified and treated with different LCE concentrations (0.5, 1.0, 2.5 and 5.0%). Two hosts of TMV (Nicotiana glutinosa L. and N. tabacum L.) were mechanically inoculated with the LCE-treated TMV preparations and antiviral effects were assessed by measuring different disease parameters in the plants including infection rate, number of local lesion, symptom index, and virus accumulation. These parameters were significantly reduced when LCE was used to treat the TMV preparation or it was applied 24 h before TMV inoculation. An inverse relationship was found between LCE concentrations and various studied parameters. Application of LCE 24 h after TMV inoculation had no significant effect on disease parameters suggesting that LCE directly affects TMV rather than activating plant defence system. The results showed that licorice can be a promising source of novel antiviral compounds againts TMV.
Keywords: disease parameters; mechanical inoculation; local lesion; systemic infection